2019
DOI: 10.1111/risa.13357
|View full text |Cite
|
Sign up to set email alerts
|

Out of Sight, Out of Mind? Geographic and Social Predictors of Flood Risk Awareness

Abstract: The persistent gap in flood risk awareness in Canada, and elsewhere in North America, is a continual source of worry for researchers and emergency managers; many people living in at‐risk places are simply unaware of risks and of their proximity to hazards. This study seeks to understand which residents were aware of flood risk, using unique representative survey data of Calgary residents living in the city's flood‐prone neighborhoods collected after the devastating and costly 2013 Southern Alberta Flood. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
4
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 55 publications
(75 reference statements)
0
10
4
3
Order By: Relevance
“…Older people have higher levels of personal risk perception, which is in line with Knocke and Kolivras (2007) and Kellens et al (2011) and in contrast to Botzen et al (2009) and Salvati et al (2014). In contrast to Liu et al (2018) and Gray‐Scholz et al (2019) the results of this study showed that low education levels are associated with high levels of personal risk perception. Similar results were found in Botzen et al (2009) and Frondel et al (2017).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Older people have higher levels of personal risk perception, which is in line with Knocke and Kolivras (2007) and Kellens et al (2011) and in contrast to Botzen et al (2009) and Salvati et al (2014). In contrast to Liu et al (2018) and Gray‐Scholz et al (2019) the results of this study showed that low education levels are associated with high levels of personal risk perception. Similar results were found in Botzen et al (2009) and Frondel et al (2017).…”
Section: Discussioncontrasting
confidence: 99%
“…This may also influence the determinants of risk perception and mitigation behaviour. Additional reasons for the low level of personal risk perception can be the high degree of trust in technologies and the improved level of flood protection over time (Gray‐Scholz et al, 2019). Walker and Burningham (2011) and Armas et al (2015) concluded that poorer and less educated people are more exposed to flood risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations